2003
DOI: 10.1046/j.1365-2826.2003.00989.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Melatonin in the Regulation of Human Circadian Rhythms and Sleep

Abstract: The circadian rhythm of pineal melatonin is the best marker of internal time under low ambient light levels. The endogenous melatonin rhythm exhibits a close association with the endogenous circadian component of the sleep propensity rhythm. This has led to the idea that melatonin is an internal sleep "facilitator" in humans, and therefore useful in the treatment of insomnia and the readjustment of circadian rhythms. There is evidence that administration of melatonin is able: (i) to induce sleep when the homeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
359
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 600 publications
(395 citation statements)
references
References 47 publications
10
359
0
6
Order By: Relevance
“…In contrast, the circadian component of the twoprocess model is not driven by prior sleep-wake duration but is rather an intrinsic, ''internal clock'' system responsible for regulating the daily, 24-h rhythmic cycle. The secretion of melatonin, a hormone produced by the pineal gland in humans, is reliably linked to the circadian system (Cajochen et al 2003;Klerman et al 2002). These homeostatic sleep-wake and circadian systems ideally work in sync to optimally regulate sleep, but this balance is often disrupted by biological, psychosocial, and contextual changes encountered in adolescence.…”
Section: Biological Factorsmentioning
confidence: 99%
“…In contrast, the circadian component of the twoprocess model is not driven by prior sleep-wake duration but is rather an intrinsic, ''internal clock'' system responsible for regulating the daily, 24-h rhythmic cycle. The secretion of melatonin, a hormone produced by the pineal gland in humans, is reliably linked to the circadian system (Cajochen et al 2003;Klerman et al 2002). These homeostatic sleep-wake and circadian systems ideally work in sync to optimally regulate sleep, but this balance is often disrupted by biological, psychosocial, and contextual changes encountered in adolescence.…”
Section: Biological Factorsmentioning
confidence: 99%
“…Since then numerous laboratory studies under stringent conditions clearly demonstrated that administration of melatonin acutely affects sleep and wakeful ness in humans. Exogenous melatonin elicits all the physiological effects which occur in the evening during endogenous melatonin secretion (for a review, see Cajochen et al, 2003). Indeed, exogenous melatonin is most effective when endogenous levels are low during the biological day.…”
Section: B Effects Of Exogenous Melatonin On Human Sleep and Wakefulmentioning
confidence: 99%
“…Regarding antidepressants, some of the therapeutic properties of selective serotonin (5-HT) reuptake-inhibiting (SSRI) drugs can be related to the 5-HT 2C receptor subtype, and it is interesting to observe that 5-HT 2C receptor agonists in the rat SCN mimic the effects of light [50]. Serotonergic drugs may thus improve entrainment.…”
Section: Chronobiological Treatments For Sleepiness and Depressionmentioning
confidence: 99%